STUDI GERAKAN TANAH DI DESA NGETOS, KECAMATAN NGETOS, KABUPATEN NGANJUK - Hendra Bahar; Yanira Artawijaya (Jurnal Geosaintek, 2024)
Landslides, for example in the incident in Selopuro Hamlet, Ngetos Village, Ngetos District, Nganjuk Regency, East Java Province, on Sunday, 14 February 2021, at 18.00 WIB, a landslide from the upper slopes hit the settlements below, Therefore, this study aims to determine the dominant factors that influence the occurrence of landslides in the Ngetos Village, as well as in which areas have the same potential for landslides as in Ngetos Village. The research was carried out by analyzing using the overlapping technique (overlay) of Geographic Information Systems (GIS). Based on the zoning of the susceptibility of ground movement, there are 3 (three) locations in the study location that are vulnerable to ground movement, namely Ngetos Village and Suru Village in Ngetos District, and Macanan Village in Loceret District, Ngajuk Regency. The causes of landslides besides the factors of slope, rainfall, and vegetation, are also caused by the type of lithology (rock/soil) in the form of weathered andesite igneous rock which is quite thick, as well as the presence of cracks on the top of the hill at the study site.